Medicinal Value of Poisonous Plants - A Review Article - Devi, Rajni; Prajapati, Munna Lal; Sason, Rajveer; Kumar, Sanjeev (International Research Journal of Ayurveda & Yoga, 2022)
Background : Since the Ayurveda is a centre for many therapeutic herbs, However, certain plants are poisonous by nature, making it impossible to consume them without purification . If used properly, these deadly plants are incredibly beneficial. Various techniques are suggested in Ayurvedic writings for the Shodhana of toxic plants. Many ailments, such as Pandu, Jwara, Aaamvata, etc., are treated with plants like Vatsanabha. Kuchla is used to treat a number of illnesses, including Grahani, Unmada, and Adhmaan. Both humans and animals have frequently been observed ingesting these toxic plants. These poisonous plants have the potential to cause accidental, homicidal and suicidal deaths. Aim: By learning about the medicinal properties of dangerous plants, this project aims to raise public knowledge about them. Material And Method: consulted from a range of databases, books, websites, and publications. Result: Poisonous plant classification was done. These deadly plants’s typical chemical components are outlined. Their mode of action has been documented. The Shodhana of these toxic plants have been described These poisonous plants have been used therapeutically. Discussion and Conclusion : This entire investigation came to the conclusion that, when used properly, deadly plants can have medical value. These toxic herbs are employed in a variety of compositions with special care. The knowledge of toxicity and usefulness of the poisonous plants are the main concern in present day scenario.